2021
DOI: 10.1016/j.jaad.2020.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for thick melanoma among veterans: A cross-sectional study

Abstract: Bold text denotes significance (P \ .05). IQR, Interquartile range. *P values were calculated with 2 tests except age, which was calculated with 1-way analysis of variance. y Age is modeled as a continuous variable, with the range as 19 to 100 years. z Excludes patients with a visit 6 months before melanoma diagnosis.x Excludes patients with visits at 6 or 12 months before melanoma diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Specifically, the article references our prior study, which found that Veterans who were older, Black, Hispanic, North Atlantic/Pacific residents, and had extra-truncal tumors were more likely to have a thick melanoma ([2 mm). 2 We agree with the author's assertion that dermatologists play a crucial role in eliminating melanoma care disparities. Additionally, we argue that these disparities are multifaceted and extend beyond issues solely with health care access and insurance status, as evidenced in the Veteran Affairs (VA) population.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Specifically, the article references our prior study, which found that Veterans who were older, Black, Hispanic, North Atlantic/Pacific residents, and had extra-truncal tumors were more likely to have a thick melanoma ([2 mm). 2 We agree with the author's assertion that dermatologists play a crucial role in eliminating melanoma care disparities. Additionally, we argue that these disparities are multifaceted and extend beyond issues solely with health care access and insurance status, as evidenced in the Veteran Affairs (VA) population.…”
supporting
confidence: 63%
“…Interestingly, we also found that Veterans who had regular dermatology visits within 6 or 12 months of diagnosis were less likely to have thick melanoma, highlighting the importance of routine screening in at-risk populations. 2 Thus, despite having equal insurance and health care access, disparities still exist across racial, ethnic, and geographic groups. These findings necessitate further consideration of other factors that complicate disparities among patients with melanoma, in addition to access to care and insurance status.…”
mentioning
confidence: 99%